Associations between physical activity and depressive symptoms in women - Salmon Jo; Ball Kylie; Teychenne Megan (BMC, 2008)
Abstract Background The high prevalence of depression in women is an increasing public health concern. Although studies have found associations between physical activity (PA) and depression, little is known about the optimal domain, dose and social context of PA for reducing the risk of depression. This study aimed to investigate associations between specific components of PA (domain, dose and social context) and odds of depressive symptoms in women. Methods The sample included 1,501 women, aged 18-65. Analyses were performed using cross-sectional data collected from a mail-out survey in 2004. The survey included self-report measures of PA behaviours and depressive symptoms. Crude and adjusted (age, marital status and physical health) odds ratios (OR) and 95% confidence intervals (CI) were calculated for each component of PA and odds of depressive symptoms using logistic regression analyses. Results Those who reported more than 3.5 hours leisure-time PA per week had lower odds of depressive symptoms when compared to those who undertook less than this. No other domains of PA (eg. work-related, transport-related or domestic activity) were associated with odds of depressive symptoms. Odds of depressive symptoms were lower among women who reported more than 1.5 hours of moderate-intensity (OR = 0.67, CI = 0.45-0.98) or more than 1.75 hours vigorous-intensity (OR = 0.60, CI = 0.42-0.84) leisure-time PA per week. Being discouraged to be active by others was associated with higher odds of depressive symptoms (OR = 2.28, CI = 1.00-5.16), whilst being active with a family member was associated with lower odds of depressive symptoms (OR = 0.61, CI = 0.43-0.87). Conclusion Acknowledging the cross-sectional design, these findings suggest that the domain and social context of PA may be more important for mental health among women than simply the total dose of PA.